Effect of Sowing Date on Growth and Yield Performance of Sweet Melon (Cucumis melo L.) in Arid Field Conditions of Ghayathi, UAE - Arshad, Imran; Philip, Phiji Jacob; AlMansoori, Mubarak Ahmed Saleh; Khan, Zaheer Ahmed (PSM Biological Research, 2025)
A field experiment was conducted in spring 2025 in Ghayathi, Al Dhafra region, Abu Dhabi, UAE, to evaluate the effect of sowing date on the growth and yield performance of sweet melon under arid open-field conditions. The study used a randomized complete block design (RCBD) with three replications, comparing three sowing dates: S? (15th February), S? (1st March), and S? (15th March). Statistically significant differences (p < 0.05) were observed among treatments, with S? showing statistically superior performance over S? and S? in all measured parameters. The highest vine length (174.2 cm), number of leaves (58.3), branches (88.4), leaf area (392.6 cm²), flowers (18.6), nodes (11.8), fruits per plant (5.4), fruit weight (1.78 kg), and marketable yield (28.6 t/ha) were recorded in S?. The superior performance of this sowing window is attributed to favorable climatic conditions during the early growth and reproductive phases. These results highlight the importance of sowing date as a critical agronomic factor influencing crop performance in desert environments. Based on the findings, sowing sweet melon around 1st March (S?) is recommended to maximize productivity in Ghayathi and similar arid agroclimatic zones.